Intra- and inter-rater reliability of thoracic spine mobility and posture assessments in subjects with thoracic spine pain - Takatalo, Jani; Ylinen, Jari; Pienimäki, Tuomo; Häkkinen, Arja (BMC musculoskeletal disorders, 2020)
Background The thoracic spine (TS) has been neglected in the study of the spine despite its essential role in the stability and posture of the entire spinal complex. Therefore, there is an inevitable need to investigate the reproducibility of different thoracic spinal posture measures used in subjects with TS pain. Methods Thirty-two subjects (16 females and 16 males, mean age 39 years) were evaluated by two physiotherapists on the same day to gauge inter-rater reliability and on two consecutive days to gauge intra-rater reliability. TS posture was assessed by observation, and thoracic spine mobility was measured by manual assessment of segmental flexion and extension mobility in a seated position. Additionally, posterior-to-anterior accessory mobility in a prone position was assessed manually. Moreover, cervicothoracic flexion in a seated position, thoracic posture, and thoracic flexion and extension mobility in a standing position were assessed with a tape measure, and flexion and extension mobility in a seated position and TS posture in seated and standing positions were measured with an inclinometer. The intraclass correlation coefficient (ICC), standard error of measurement (SEM), mean difference (MD), Bland-Altman (B&A) plot features and coefficient of repeatability (CR) were calculated. Results The mean and standard deviation (SD) of the duration of TS pain was 22 (SD 45) months, with the intensity of pain being rated at 27 (SD 21) mm on a visual analogue scale (VAS). Intra-rater reliability was very strong (ICC ≥ 0.80) for the evaluation of seated and standing upper TS posture, standing whole TS posture and seated lower TS posture with an inclinometer. Moreover, TS posture evaluation with a measuring tape, posture inspection in a seated position, and manual assessment of segmental extension were found to have very strong intra-rater reliability. Inter-rater reliability was very strong for inclinometer measurements of standing and seated upper TS posture as well as standing whole TS posture. Conclusion Intra-rater reliability was higher than inter-rater reliability in most of the evaluated measurements. Overall, posture measurements with an inclinometer were more reliable than mobility measurements with the same instrument. The manual assessments can be used reliably when same evaluator performs the examination. Trial registration Clinical Trials, NCT01884818. Registered 24 June 2013, https://clinicaltrials.gov/ct2/show/NCT01884818?cond=thoracic+spine&cntry=FI&rank=1